2020
DOI: 10.21608/asnj.2020.80500
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses’ Knowledge and Practice for Patients Undergoing a Bronchoscopy [Suggested Nursing Care Guidelines]

Abstract: Aim: to assess nurses' knowledge and practice for patients undergoing bronchoscopy procedures and design suggested nursing care guidelines for those nurses. Design: descriptive research design was utilized in this study. Setting: The study was conducted on 40 nurses at bronchoscopy unit of the chest department, at Assiut University hospital. Tools: A structured interview questionnaire sheet for nurses. Including: Demographic data, an observation checklist for nurses and develop suggested nursing care guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Nursing students have varying degrees of education. This conclusion corroborates the findings of a research conducted by (Ahmed et al, 2020) said in their research that they wanted to measure nurses' knowledge on preventing Infections of central venous catheters were recorded in critical care units at Baghdad Teaching Hospitals. that (52% of the research sample) were between the ages of 20 and 29 years.…”
Section: Discussionsupporting
confidence: 85%
“…Nursing students have varying degrees of education. This conclusion corroborates the findings of a research conducted by (Ahmed et al, 2020) said in their research that they wanted to measure nurses' knowledge on preventing Infections of central venous catheters were recorded in critical care units at Baghdad Teaching Hospitals. that (52% of the research sample) were between the ages of 20 and 29 years.…”
Section: Discussionsupporting
confidence: 85%
“…Of the 14 studies, 11 assessed nurses' practices concerning VTE prophylaxis (Ahmed et al, 2020; Al‐Mugheed & Bayraktar, 2018; Amira et al, 2018; Antony et al, 2016; Gaston & White, 2013; Lau et al, 2017; Lee et al, 2014; Ma et al, 2018; Oh et al, 2016; Songwathana et al, 2011; Walker et al, 2010). The practice levels of the nurses on VTE prophylaxis were categorized as poor, unsatisfactory, and moderate.…”
Section: Resultsmentioning
confidence: 99%
“…The practice levels of the nurses on VTE prophylaxis were categorized as poor, unsatisfactory, and moderate. Of the 11 studies, five reported nurses had poor VTE practice levels (Ahmed et al, 2020; Al‐Mugheed & Bayraktar, 2018; Amira et al, 2018; Antony et al, 2016; Ma et al, 2018). Three studies reported that nurses had VTE practice levels after education (Gaston & White, 2013; Lau et al, 2017; Walker et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations